Transformation of Tetrafluoroethylene Using Transition-Metal Complexes - Doi, Ryohei; Zhou, Yuyang; Ogoshi, Sensuke (Synthesis, 2022)
Tetrafluoroethylene (TFE) is an industrial organofluorine feedstock that is used predominantly to fabricate fluorinated polymers. TFE exhibits excellent potential as a building block for synthesizing organofluorine compounds, which are increasingly gaining attention as functional materials, pharmaceuticals, and agrochemicals. In particular, the use of transition-metal complexes in the transformation of TFE is of great interest, considering their widespread use in syntheses of organofluorine compounds over the last few decades. This review highlights studies on the transformation of TFE into organofluorine compounds using transition-metal complexes, except for polymerizations. Our review covers cross-coupling reactions via C–F bond cleavage, fluoroalkylation reactions, multicomponent couplings, and olefin metathesis.1 Introduction2 Palladium Complexes3 Copper Complexes4 Nickel Complexes5 Ruthenium Complexes6 Rhodium Complexes7 Summary and Perspective
Keywords: tetrafluoroethylene; palladium; copper; nickel; ruthenium; rhodium; organofluorine compounds